Impact of portal vein infiltration and type of venous reconstruction in surgery for borderline resectable pancreatic cancer. Issue 11 (22nd August 2017) - Ravikumar, R; Sabin, C; Abu Hilal, M; Al-Hilli, A; Aroori, S; Bond-Smith, G; Bramhall, S; Coldham, C; Hammond, J; Hutchins, R; Imber, C; Preziosi, G; et al.
Abstract: Background: The International Study Group of Pancreatic Surgery (ISGPS) recommends operative exploration and resection of pancreatic cancers in the presence of reconstructable mesentericoportal axis involvement. However, there is no consensus on the ideal method of vascular reconstruction. The effect of depth of tumour invasion of the vessel wall on outcome is also unknown. Methods: This was a retrospective cohort study of pancreaticoduodenectomy with vein resection for T3 adenocarcinoma of the head of the pancreas across nine centres. Outcome measures were overall survival based on the impact of the depth of tumour infiltration of the vessel wall, and morbidity, in-hospital mortality and overall survival between types of venous reconstruction: primary closure, end-to-end anastomosis and interposition graft. Results: A total of 229 patients underwent portal vein resection; 129 (56·3 per cent) underwent primary closure, 64 (27·9 per cent) had an end-to-end anastomosis and 36 (15·7 per cent) an interposition graft. There was no difference in overall morbidity (26 (20·2 per cent), 14 (22 per cent) and 9 (25 per cent) respectively; P = 0·817) or in-hospital mortality (6 (4·7 per cent), 2 (3 per cent) and 2 (6 per cent); P = 0·826) between the three groups. One hundred and six patients (47·5 per cent) had histological evidence of vein involvement; 59 (26·5 per cent) had superficial invasion (tunica adventitia) and 47 (21·1 per cent) had deep invasion (tunica media or intima). Median survival was 18·8 months for patients who had primary closure, 27·6 months for those with an end-to-end anastomosis and 13·0 months among patients with an interposition graft. There was no significant difference in median survival between patients with superficial, deep or no histological vein involvement (20·8, 21·3 and 13·3 months respectively; P = 0·111). Venous tumour infiltration was not associated with decreased overall survival on multivariable analysis. Conclusion: In this study, there was no difference in morbidity between the three modes of venous reconstruction, and overall survival was similar regardless of tumour infiltration of the vein. Abstract : No difference between type of reconstruction